Uptake of early infant diagnosis in Thailand's national program for preventing mother‐to‐child HIV transmission and linkage to care, 2008–2011. Issue 1 (9th March 2016) - Naiwatanakul, Thananda; Voramongkol, Nipunporn; Punsuwan, Niramon; Lolekha, Rangsima; Gass, Robert; Thaisri, Hansa; Leechanachai, Pranee; Wolfe, Mitchell; Boonsuk, Sarawut; Bhakeecheep, Sorakij
Abstract : Introduction: Early infant diagnosis (EID) has been a component of Thailand's prevention of mother‐to‐child HIV transmission (PMTCT) programme since 2007. This study assessed the uptake, EID coverage, proportion of HIV‐exposed infants receiving a definitive HIV diagnosis, mother‐to‐child transmission (MTCT) rates and linkage to HIV care and treatment. Methods: Infant polymerase chain reaction (PCR) testing data from the National AIDS Program database were analyzed. EID coverage was calculated as the percentage of number of HIV‐exposed infants receiving ≥1 HIV PCR test divided by the number of HIV‐exposed infants estimated from HIV prevalence and live‐birth registry data. Definitive HIV diagnosis was defined as having two concordant PCR results. MTCT rates were calculated based on infants tested with PCR and applied as a best‐case scenario, and a sensitivity analysis was used to adjust these rates in average and worst scenarios. We defined linkage to HIV care as infants with at least one PCR‐positive test who were registered with Thailand's National AIDS Program. Chi‐squared tests for linear trend were used to analyze changes in programme coverage. Results: For 2008 to 2011, the average EID coverage rate increased from 54 to 76% ( p <0.001), with 65% coverage (13, 761/21, 099) overall. The number of hospitals submitting EID samples increased from 458 to 645, and the percentage of community hospitals submitting samples increased from 75 to 78% ( p =0.044). A definitive HIV diagnosis was made for 10, 854 (79%) infants during this period. The adjusted MTCT rates had significantly decreasing trends in all scenarios. Overall, an estimated 53% (429/804) of HIV‐infected infants were identified through the EID programme, and 80% (341/429) of infants testing positive were linked to care. The overall rate of antiretroviral treatment (ART) initiation within one year of age was 37% (157/429), with an increasing trend from 28 to 52% ( p <0.001). Conclusions: EID coverage increased and MTCT rates decreased during 2008 to 2011; however, about half of HIV‐infected infants still did not receive EID. Most HIV‐infected infants were linked to care but less than half initiated ART within one year of age. Active follow‐up of HIV‐exposed infants to increase early detection of HIV infection and early initiation of ART should be more widely implemented.